MODERN CONCEPTS OF PELVIC ADHESIONS’ ETIOLOGY AND PATHOGENESIS AT REPRODUCTIVE AGE WOMEN - A. A. Alekseev; A. N. Sulima (Медицинский вестник Юга России, 2016)
The literature review presents the modern data on the pelvic adhesions’ etiology and pathogenesis at women of reproductive age. Pelvic adhesion is a dynamic differentiated cell vascularized structure. Development of an active inflammatory process, which involving cells and proinflammatory mediators may be into a stage of tissue remodeling, collagen formation, that is the initial symptoms of adhesions. A vicious circle and a cascade of mutually supporting changes leads to adhesive disease and patients’ disability.